Cinema of discontent : representations of Japan's high-speed growth - Sasaki, Tomoyuki (State University of New York Press, 2022)
Uses popular films to reveal the tensions generated during Japan's postwar ""economic miracle,"" challenging the prevailing view that it was a story of great national success.
Keywords: History in motion pictures.; Economics in motion pictures.; Motion pictures -- Japan -- History -- 20th century.; Japan -- In motion pictures.; Performing arts.; Video recordings.; Electronic books.; Histoire au cinéma.; Économie politique au cinéma.; Cinéma -- Japon -- Histoire -- 20e siècle.; Arts du spectacle.; Vidéos.; Livres numériques.; performing arts (discipline); video recordings (physical artifacts); e-books.; PERFORMING ARTS / Film & Video / History & Criticism.; Economics in motion pictures; History in motion pictures; Motion pictures; Japan; 1900-1999; History